INEQUALITIES IN ACCESS TO COVID-19 VACCINES AND POTENTIAL SOLUTIONS FOR LOW- AND MIDDLE-INCOME COUNTRIES (Proceedings of the Global Public Health Conference, 2023)
Despite approved vaccines against Coronavirus Disease 2019 (COVID-19) having been available for more than a year, low- and middle-income countries (LMICs) have been unequally affected by low vaccination coverage. The overarching goal of the COVID-19 Vaccine Global Access (COVAX) mission is to ensure that all countries can secure enough doses to vaccinate 20% of their population before any one country vaccinates more than 20% of their population. However, limited resources, poor infrastructure and constrained financial capabilities have contributed to challenges in producing, acquiring, and distributing vaccines amongst developing nations. This review was aimed at identifying inequalities and proposing mitigation measures to minimize disparities in access and distribution of COVID-19 vaccines in LMICs. A narrative literature review of scientific papers published during 2020-2022 was carried out accessing databases including Google Scholar and Medline (PubMed). Factors affecting access to COVID-19 vaccine research, manufacturing, procurement, and deployment capabilities were studied. The results revealed that the combined populations in LMICs that make up 84% of the global population were able to secure only 30% of the COVID vaccine doses produced in 2021. Alternatively, high-income countries make up 16% of the global population and had purchased 70% of vaccine doses produced in 2021. The causes were multifactorial and included challenges involving production, procurement and allocation, deployment, accessibility, and vaccine hesitancy. Mitigation measures include better manufacturing or procurement capabilities based on shared intellectual property and aid as well as better storage systems for temperature-sensitive vaccine deployment. Vaccine hesitancy can be mitigated by leveraging the influences of well-informed health care workers, social workers, political, religious and community leaders who can help dispel misinformation and improve vaccine acceptance among the masses. Reducing disparities in vaccination coverage of LMICs is an important step towards the global progress in combating the pandemic and especially in preventing the spread of potential viral variants.
Keywords: COVID-19; Vaccine; Low- and Middle-Income Countries (LMICs); Disparities